2015
DOI: 10.1093/ijnp/pyv012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tryptophan on Everyday Interpersonal Encounters and Social Cognitions in Individuals with a Family History of Depression

Abstract: Background:Individuals with a family history of depression show subtle abnormalities in the processing of social stimuli. This could negatively affect their interpersonal functioning and contribute to their depression risk. Repeated administration of the serotonin precursor tryptophan has previously been shown to increase agreeable behavior and reduce quarrelsome behavior in irritable people, who are also considered at risk for depression.Methods:To examine the effects of tryptophan on social functioning in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Our results could be in agreement with those which found that a family history of depression was associated with poor social functioning . This fact may be due to the existence of subtle impairments in the processing of emotional stimuli . Further longitudinal, genetic studies and research with unaffected relatives are needed to gain a better insight into the trajectories of social cognitive deficits in BD.…”
Section: Discussionsupporting
confidence: 92%
“…Our results could be in agreement with those which found that a family history of depression was associated with poor social functioning . This fact may be due to the existence of subtle impairments in the processing of emotional stimuli . Further longitudinal, genetic studies and research with unaffected relatives are needed to gain a better insight into the trajectories of social cognitive deficits in BD.…”
Section: Discussionsupporting
confidence: 92%
“…For example, there is evidence that TRP supplementation can promote prosocial behaviour in economic decision-making tasks ( 22 ) . Somewhat counterintuitively, a more recent study, in which 1 g TRP was given three times daily for 14 d to those with a family history of depression, found increased quarrelsomeness and reduced agreeableness (at home), but improved mood, compared with placebo ( 86 ) . This was interpreted as possibly reflecting the development of more control in social interactions at home.…”
Section: Effects Of L-tryptophan Administration and Supplementationmentioning
confidence: 97%
“…This study is part of a more comprehensive project assessing the role of serotonin in social behaviour; an overview of all included measures can be found at Clinical Trials.gov (NCT020051530). Eleven FH+ individuals also participated in a related project (Hogenelst et al, 2015; NCT02051569).…”
Section: Methodsmentioning
confidence: 99%